Ferramenta para análise de dados de temperatura de mancais de motores diesel ferroviários - Martelli, Gabriel (2024)
This work addresses the optical temperature monitoring of bearings in large diesel engines for railway use, with the aim of developing a new methodology for analyzing the collected data. A system based on fiber optic Bragg gratings, distributed inside the crankcase of diesel engines, was used to measure the temperature of the lubricant oil coming thru each engine bearing. The data collected by this system were used to develop a tool capable of monitoring the emergence of failures in main or rod engine bearings through temperature variations. New forms of graphical visualization, both for the sensor set or for an individual sensor, are presented and interpreted, and can be used by maintainers as support tools in decision-making regarding the predictive maintenance process of the locomotive. The analysis of approximately two thousand hours of operation demonstrated that the tool has the capacity to detect failures at an early stage, monitor the evolution of these failures and indicate the ideal time to perform maintenance, without putting the equipment at risk and avoiding unscheduled exams that cause financial losses to the company.